Parasitic infection prevalence in tuberculosis patients and their household contacts in the Littoral Region of Cameroon - Lucy Cho Nchang; Chefor Magha; Patience Agwa Fonong; Narcisse Victor Tchamatchoua Gandjui; Nancielle Mbiatong Tchatat; Desmond Akumtoh Nkimbeng; Frank Noel Nietcho; Juluis Visnel Foyet; Fanny Fri Fombad; Tatiana Djikeussi Katcho; Jerome Fru Cho; Achim Hoerauf; et al. (Parasite Epidemiology and Control)
Background: Parasitic infections are known to suppress the cell mediated immunity that protects against tuberculosis. The status of parasitic infections among bacteriologically confirmed tuberculosis patients and their household contacts in Cameroon is not well established. This study aimed at reporting the status of parasitic infections in TB patients and their household contacts with keen interest in associated risk factors to disease exposure. Methodology: This was a hospital based cross-sectional descriptive study carried out with newly diagnosed active tuberculosis (TB) patients and their household contacts in the Littoral Region of Cameroon. Socio-demographic data and associated factors were collected using structured questionnaires. Blood, stool, urine and skin snip samples were collected following standard guidelines for investigation of parasitic infections. Descriptive analysis was performed, bivariate analysis was computed and a multivariable analysis was done to provide adjusted odds ratios (AOR). Results: A total of 712 TB patients and 472 household contacts were recruited. The overall prevalence of parasitic infections in TB patients was 25.84 % (184/712) and household contacts was 31.36 % (148/472). Blood protozoan (Plasmodium falciparum) infection among active TB patients (20.22 %) and their household contacts (26.27 %) was the most frequently detected parasitic infection. Loa loa was the predominant helminth species seen among active TB patients while Schistosoma mansoni was the predominant helminth infection detected in household contacts. TB patients and household contacts living in urban areas had lower odds of being associated with helminth infections (AOR 0.2, 95 % CI: 0.10–0.40; p ˂ 0.0001 and AOR 0.11, 95 % CI: 0.04–0.27; p ˂ 0.0001 respectively) as compared to those residing in rural areas. Conclusion: We observed that 31 % of the TB patients and household contacts are infected with parasites including P. falciparum, Loa loa and Since helminths can downregulate immune responses against bacterial infections and thus affect treatment efficacy, we recommend that diagnosis of parasitic infections should be included during TB diagnosis and treatment programmes, especially in rural areas.